Pengaruh Self Eficacy, Self Esteem, Dukungan Sosial Terhadap Stres AkademikMahasiswa Tingkat Akhir - Hidayat, Erik Ibnu; Ramli, M.; Setiowati, Arbin Janu (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Academic stress is an imbalance between task completion and one's ability to complete it. Academic stress in higher education often occurs in students, especially final year students. The inability to complete the task ultimately makes academic stress caused by factors of self efficacy, social support and self-esteem that is not owned by the students themselves. This study aim to understand the majority of these factors towards student academic pressure. The research is quantitative correlational, in which the research sample used is the students of the final semester of 2015 and 2016 in the Guidance and Counseling study program with a total of 86 people, with a scale of instruments Social Support, Self Efficicacy, Self Esteem, and Academic Stress that have been available at Morgan-Jinks Student Efficacy Scale (MJSES), Self Esteem Inventory (SEI), Interpersonal Supports Evaluation List (ISEL), and academic stress scale. The results showed that self-efficacy did not have a significant effect on academic stress; (2) self-esteem gives an insignificant influence in accademic stress; (3) social support for student academic stress; (4) academic stress can be represented by self-efficacy, and support social, and self-esteem by 29.9%, or in other words supporting self-efficacy, self-esteem, and social support for academic stress by 29.9%, also by 70, 1%, (5) social supports, self efficacy, self-esteem, and social supports for academic stress have an effective contribution to variable self efficacy to academic stress by 6.0%; (6) effective contribution of self-esteem variables to academic stress by 0.6%; (7) the contribution of an effective variable of social support to academic stress by 27.0%.Abstrak: Stres akademik merupakan ketidakseimbangan antara tuntutan tugas dengan kemampuan seseorang untuk menyelesaikannya.. Stres akademik diperguruan tinggi sering terjadi pada mahasiswa, terutama mahasiswa tingkat akhir. Ketidakmampuan menyelesaikan tugas akhir sehingga menimbulkan kondisi stress akademik disebabkan oleh faktor self efficacy dukungan sosial dan self esteem yang tidak dimiliki oleh mahasiswa itu sendiri. Penelitian ini untuk menjawab pertanyaan penelitian yaitu korelasi antara ketiga faktor terebut terhadap munculnya stress akademik mahasiswa. Jenis penelitian yang digunakan adalah kuantitatif korelasional, dengan sampel 86 mahasiswa program studi Bimbingan dan Konseling. Instrumen yang digunakan skala Self Eficacy, Self Esteem, Dukungan Sosial dan Stress akademik yang sudah diadaptasi Morgan-Jinks Students Efficacy Scale (MJSES), Self Esteem Inventory (SEI), Interpersonal Support Evaluation List (ISEL), dan skala stress akademik. Hasil penelitian menunjukan self efficacy memberikan pengaruh yang signifikanterhadap stres akademik; (2) self esteem memberikan pengaruh yang tidak signifikan terhadap stres akademik; (3) dukungan sosial secara signifikanÂ  memberikan pengaruh terhadap stress akademik mahasiswa; (4) stres akademikmampu direpresentasikan oleh self efficacy, self esteem, dan dukungan sosial sebesar 29.9%, atau dengan kata lain kontribusi self efficacy, self esteem, dan dukungan sosial terhadap stres akademiksebesar 29.9%, sedangkan sisanya sebesar 70.1%, (5) self efficacy, self esteem, dan dukungan sosial terhadap stres akademik memiliki sumbangan efektif variabel self efficacy terhadap stres akademik sebesar 6.0%; (6) sumbangan efektif variabel self esteem terhadap stres akademik sebesar 0.6%; (7) sumbangan efektif variabel dukungan sosial terhadap stres akademik sebesar 27.0%.Â